2014
DOI: 10.5812/ircmj.13395
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Factors Explaining the Referral Behavior of Iranian Family Physicians

Abstract: Background:The recently developed policy of the family practice program in rural regions of Iran faced some challenges such as inefficient referral system. The health insurance organizations (purchaser) and health policy makers are concerned about the high rate of patient referrals from family physicians to specialists due to imposing unnecessary services and costs.Objectives:This study examined utility of the theory of planned behavior to explain intention of Iranian family physicians to reduce referral rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…reported that some FPs feel that they have low control on referral decisions due to the social pressure. [ 10 ] In the current study, the participants argued how this issue was also solved through the instructions approved by these executive meetings which limited the referrals up to 20% of total FP visits.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…reported that some FPs feel that they have low control on referral decisions due to the social pressure. [ 10 ] In the current study, the participants argued how this issue was also solved through the instructions approved by these executive meetings which limited the referrals up to 20% of total FP visits.…”
Section: Discussionmentioning
confidence: 97%
“…[ 8 9 ] Gradually, health system failed to respond to the emerging needs of the population because of high burden of noncommunicable diseases, public expectation to access qualified physicians, and fast-growing technologies. [ 10 11 ] Therefore, the Ministry of Health and Medical Education (MOHME) initiated a series of health sector reforms, including the pilot phase of FP program as a basic health plan in rural areas based on the fourth 5-year national development plan in 2005. [ 12 13 14 ] These reforms in rural areas and small cities with populations under 20,000 individuals made very sharp improvements, especially in major health indicators, such as maternal mortality, life expectancy, and the control of infectious diseases.…”
Section: Introductionmentioning
confidence: 99%